Teacher Travelers in Jamaica: Using Study Tours as Field-Based Experiences - Foster, Karen (Educational (Re)naissance, 2014)
In his article titled “Why We Travel,” Pico Lyer clarified a clear distinction between travelers and tourists with “travelers” leaving their assumptions behind and “tourists” complaining that “nothing is the same way it is at home.” When a group of six undergraduate students and one faculty member from the University of Central Missouri (UCM) spent a week teaching 125 students a day in an at-risk youth camp in Petersfield, Jamaica in July, 2013, we were immersed in the local culture enabling us to experience Jamaica more as teacher “travelers” than “tourists” in many ways.